2006
DOI: 10.1207/s15324834basp2804_10
|View full text |Cite
|
Sign up to set email alerts
|

Anti-American Sentiment and America's Perceived Intent to Dominate: An 11-Nation Study

Abstract: Perceptions of America as a powerful but malevolent nation decrease its security. On the basis of measures derived from the stereotype content model (SCM) and image theory (IT), 5,000 college students in 11 nations indicated their perceptions of the personality traits of, intentions of, and emotional reactions to the United States as well as their reactions to relevant world events (e.g., 9/11). The United States was generally perceived as competent but cold and arrogant. Although participants distinguished be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…However, at an international relations level, such differentiation might be important. Glick et al. (2006) found that across different countries, participants expressed more contempt toward the U.S. government compared to American citizens, but in most samples there were no differences in levels of admiration and envy toward these two target subgroups.…”
Section: Discussion Of Studymentioning
confidence: 95%
“…However, at an international relations level, such differentiation might be important. Glick et al. (2006) found that across different countries, participants expressed more contempt toward the U.S. government compared to American citizens, but in most samples there were no differences in levels of admiration and envy toward these two target subgroups.…”
Section: Discussion Of Studymentioning
confidence: 95%
“…These findings suggest that the findings for competence and group status may not be as universal as Glick et al (2004) suggested; rather, there may be culture-specific content in the Indian subcontinent for stereotypes derived from historical representations or narratives (see Liu & Hilton, 2005) that do not rely on internal ability attributions as a basis for establishing hegemony (see J. G. Miller, 1984).…”
Section: Warmth Versus Competencementioning
confidence: 88%
“…Status and power elevate a group's perceived competence, whereas a group's competitiveness lowers its perceived warmth. In a recent cross-cultural study, Glick et al (2004) revealed that respondents from 11 nations characterized the United States and its citizens as competent but lacking warmth. This characterization was mediated by perceptions of the nation's competitiveness.…”
mentioning
confidence: 99%
“…The SCM likewise describes patterns of resentment toward (enviable) Asians in the U.S. (15), Americans in other countries (43, 44), and politicians everywhere (45). Other enviable outgroup members (rich people, business people) specifically elicit envy-consistent Schadenfreude (malicious glee at their misfortunes), measured by self report, smile-muscle activation, and neural reward centers (46, 47).…”
Section: Validitymentioning
confidence: 99%